DECISION SUPPORT SYSTEM MENGGUNAKAN FUZZY LOGIC PADA PERSEROAN TERBATAS SAPTA INDRA SEJATI DIVISI GENERAL SUPPORT TRANSPORT - Fitri, Mega Orina; Herni, Herni (Teknosains: Media Informasi Sains dan Teknologi, 2015)
t’s not easy to implement Decision Support System (DSS) application in a company. There are many things need to be considered before a manager take a decision. And there are a few methods can be used to implement DSS applicaton.. This paper explained about how to make a DSS application by using Fuzzy Logic. The case took place in General Support Divison at PT Sapta Indra Sejati, Kalimantan Selatan. This DSS is using Fuzzy DatabaseTahanis’Model (Fuzzy Tahani).Data is obtained from library research and interviews. A Data Warehouse will be built before desain a DSS application. This application will be tested by using BlackBox Testing. The result of this testing is the application can perform well and reliable to give recommendations to help manager to take a decision for the company quickly.